The origin and evolution of LCT pegmatites in Helgeland, northern Norway: stable isotope evidence from tourmaline (δ11B) and garnet (δ18O, ∆’17O) - Schickhoff, Amelie (UiT Norges arktiske universitet, 2024)
The processes leading to formation of rare-element enriched granitic pegmatites are controversially debated amongst petrologists and economic geologists. Two contrasting genetic models discuss the necessity of a parental granitic pluton as the magma source versus an anatectic origin via partial melting of metasedimentary rocks. Geochemical tools such as the analysis of stable isotopic compositions can be applied to trace the origins and evolution of pegmatite-forming magmas. In this MSc thesis, analyses of the boron isotopic compositions of tourmaline and the triple oxygen isotopic compositions of garnet from granitic pegmatites were combined with their mineral major and trace element compositions to evaluate the tectonomagmatic evolution of the North Helgeland pegmatite field (Nordland county, northern Norway). The magmatic-hydrothermal evolution of this LCT-type pegmatite field is constrained by a more detailed investigation of the previously mined pegmatite body at Ågskardet. Tourmaline compositions in the selected pegmatite bodies vary between dravite in the upper pegmatite at Ågskardet, schorl at Grønnøya, Ørnes and in outer zones of the Ågskardet old quarry pegmatites, and F-schorl to F-rich elbaitic, tsilaisitic and F-liddicoatitic compositions in the inner zone of the Ågskardet old quarry pegmatite. Lithium contents in tourmaline increase from the outer to the inner pegmatite zones. Tourmaline from the inner zone is enriched in Sr and Pb compared to all other tourmaline crystals studied, and it shows complex replacement textures. Garnet in the North Helgeland pegmatites is dominated by almandine and spessartine components. Except for garnet from the old quarry pegmatite at Ågskardet, the garnet crystals are enriched in HREE. Tourmaline δ11B values range from -15.5 to -1.9 ‰ (± 0.9‰, 1-sigma). For tourmaline from the two pegmatite bodies at Ågskardet, the range in δ11B corresponds to values typical for S-type granites, whereas slightly heavier values were obtained for tourmaline from the pegmatites at ...